MOLECULAR DOCKING AND MOLECULAR DYNAMICS STUDIES OF ACALYPHA INDICA L. PHYTOCHEMICAL CONSTITUENTS WITH CASPASE-3 - FEBRINA, ELLIN; ALAMHARI, RYAN KHUNAM; ASNAWI, AIYI; ABDULAH, RIZKY; LESTARI, KERI; LEVITA, JUTTI; SUPRATMAN, UNANG (International Journal of Applied Pharmaceutics, 2021)
Objective: This study investigated the structure-based molecular interactions between phytochemical constituents of Acalypha indica L. and caspase-3. Methods: Thirty-three phytochemical constituents of A. indica were screened against caspase-3. The X-ray crystal structure of human caspase-3 was retrieved from https://www.rcsb.org/structure/. The molecular interactions of the phytochemicals were studied using the AutoDock 4.2 software and followed by molecular dynamics (MD) simulations using the Amber18 software. Results: From this study, 25 screened phytochemicals were found to have a better binding mode than the native ligand. Moreover, the binding stability of the top four hits evaluated by MD indicated that the hydrogen bonds in MD were quite different from the molecular docking results due to the massive receptor and ligand movement in the MD simulations. However, with the exception of stigmasterol, all ligands were able to stabilize the protein. Conclusion: This study suggested that γ-sitosterol acetate, β-sitosterol acetate, and γ-sitosterol might be able to induce caspase-3, thereby activating apoptosis. These high-affinity compounds can bind to caspase-3 more efficiently and were able to stabilize the protein. Therefore, they have the potential to be used as lead compounds in the treatment of cancer.